Membangun Jati Diri Suku Tehit Kabupaten Sorong Selatan Papua Barat - Marlina Flassy (CENDERAWASIH: Jurnal Antropologi Papua, 2020)
This article aims to analyze the identity construction of the Tehit tribe in Sorong Regency, West Papua Province. This study used a qualitative method with an ethnographic approach. The determination of informants is determined purposively, by selecting influential figures, both traditional and educational figures. The data collection technique used was in-depth interviews. Then data analysis includes the stages of data categorization, data description, and data interpretation. The results showed that the sense of identity of the Tehit tribe experienced degradation internally and externally due to practical politics and economic competition so that relations between people became loose. For this reason, the strategy developed in constructing the identity of the Teaite tribe is the socialization of tea culture and strengthening solidarity between groups, by revitalizing traditional institutions and carrying out cultural events to arouse the spirit of ethnicity of the Tehit tribe, as well as revitalizing claims to customary forests as customary rights as part of defending their identity. the Tehit tribe. then, educate among community groups and regenerate them to occupy strategic positions. Therefore, the technical culture must be made in a written document and visualized so that continuous research is needed to be included in the preparation of the Regional Budget (APBD) of South Sorong Regency